HORMONAL RISK FACTORS AFFECTING THE STAGES OF DEVELOPMENT OF MAMMARY ONTOGENESIS - Yusupjanova S. Qudratullayevna; Professor, DSc Rasulov H. A.; Dotsent, PhD Xidirova G. Ozodovna (Journals Park Publishing, 2026)
The mammary gland is a hormone-dependent member, and its development and functional status are closely related to the influence of internal factors, primarily the hormonal background. Disruption of the balance of estrogens, progesterone, prolactin and other hormones can lead to morphological changes in the gland tissue, which affects the processes of differentiation and secretion. The study of these mechanisms is of great importance in understanding the pathogenesis of mammary diseases and the development of preventive measures. Thyroid hormones are involved in the regulation of metabolic processes, reproductive function and hormonal homeostasis, which have a systemic effect on the body. The mammary gland is a hypersensitive organ to the hormone, and its functional status is determined by the complex interaction of estrogen, progesterone, prolactin and thyroid hormones. In this regard, the study of structural and functional changes in the mammary glands in women with thyroid pathology is of particular scientific and practical interest.
Keywords: T3 and T4, estrogens, progesterone, thyroid gland, thyroid hormone, prolactin.